Screening of secondary metabolites and immunostimulation potential of poly herbal formoulation (Asparagus racemosus, Mucuna pruriens, Anacyclus pyrethrum and Tribulus terristeris) in Wistar Albino rats - M. Akram,; Shifa shaffique, (International Journal of Phytomedicine, 2021)
Immune system is a defensive mechanism system which is responsible to defend against several foreign invading agents that harm individual health. It generates several types of cells which have ability to recognize, eliminate and kill all the undesirable agents. The immune system works by inhibition, multiplication, amplification, expression and induction response at different phases of immune system. Hence immunology is the most advance and recent biomedical research system which covers the prevention and treatment of wide range of medical disorders. In this study, Immunomodulatory activity of Polyherbal formulation was determined. First of all, plants methanolic extracts of Asparagus racemosus, Mucuna pruriens, Anacyclus pyrethrum, Tribulus terrestris were prepared. The methanolic extracts of each plant were taken separately in equal amount and mixed to prepare the Polyherbal formulation (PHF). Screening test was applied on PHF for quantitative analysis. Hemolytic activity, thrombolytic activity and antioxidant activity were determined on experimental animals. To demonstrate the effect of standard Immunol drug, CCl4 and polyherbal formulation extract on hematological parameters. The methanolic extract of PHF was dissolved in distilled water and the dose was selected at 100, 200 and 300 mg/kg body weight. Blood sample collected in EDTA as anticoagulant were processed to determine the effect of PHP on selected hematological parameters including hemoglobin (Hb), red blood cell counts (RBCs), white blood cells (WBCs) count and Platelets count. Liver enzymes like transaminases (ALT and AST), uric acid, urea and creatinine were determined by automated photometric method to evaluate the drug safety. Serum samples were using for the estimation of Immunoglobulin M and Immunoglobulin G using enzyme linked immunosorbent assay (ELISA). Further, the C-reactive protein (CRP) was also estimated using standard protocol. Phytochemical screening of methanolic extract of polyherbal formulation showed the presence of alkaloids, tannins, flavonoids, phenols and cardiac glycosides. Bioactive constituent’s alkaloids, flavonoids and phenols were present in higher concentration. The maximum hemolysis was seen at a dose of 800μg/ml (40±0.38). The methanolic extracts of PHF were investigated for its thrombolytic activity. Addition of 800μl of streptokinase as positive control (30,000 IU/ ml) to clots and successive incubation for 90 minutes at 37 ºC showed 74.53±1.11% lysis of clot. Distilled water was considered as negative control which exhibit insignificant percentage of lysis of clot (3.74±0.51). In the study, the methanolic extract of PHF showed highest thrombolytic activity at 800μg/ml concentrations (41±0.38) when compared with streptokinase (positive control). When all the groups were compared the serum level ALT, AST, TAS, TOS and OSI 50 index, a statistically significant difference was observed between the groups. A variety of antioxidant function approaches have been suggested. During the study, it was found that induction of CCl4 increases the number of altered macrophages. However, the administration of Polyherbal extract in CCl4 intoxicated animals, the number of altered macrophages came to level. Administration of polyherbal formulation extract in control mice also showed significant reduction of changed macrophages. Immunomodulatory drugs are substances that can alter the immune function of an individual, are called immunostimulants if their immune responses are enhanced, or are called immunosuppressant’s if they decrease. These medications are most widely used in infections, allergies and cancer infections. Modern medical treatment is also far-reaching because of the economic limitations in developed countries including Pakistan. For immunomodular operations, just a few plants have been tested. The analysis indicates that many medicinal plants and marine products have immunomodulatory function, however there is little proof that their use in clinical practice is not allowed. In future work in herbal medicine, therefore, immunomodulatory agents should become more relevant.